Health related quality of life measure in systemic pediatric rheumatic diseases and its translation to different languages: an international collaboration - Moorthy, Lakshmi Nandini; Roy, Elizabeth; Kurra, Vamsi; Peterson, Margaret G. E.; Hassett, Afton L.; Lehman, Thomas J. A.; Scot, Christiaan; El-Ghoneimy, Dalia; Saad, Shereen; El Feky, Reem; Al-Mayouf, Sulaiman; Dolezalova, Pavla; et al. (Biomed Central Ltd, 2014)
Background: Rheumatic diseases in children are associated with significant morbidity and poor health-related quality of life (HRQOL). There is no health-related quality of life (HRQOL) scale available specifically for children with less common rheumatic diseases. These diseases share several features with systemic lupus erythematosus (SLE) such as their chronic episodic nature, multi-systemic involvement, and the need for immunosuppressive medications. HRQOL scale developed for pediatric SLE will likely be applicable to children with systemic inflammatory diseases.Findings: We adapted Simple Measure of Impact of Lupus Erythematosus in Youngsters (SMILEY (c)) to Simple Measure of Impact of Illness in Youngsters (SMILY (c)-Illness) and had it reviewed by pediatric rheumatologists for its appropriateness and cultural suitability. We tested SMILY (c)-Illness in patients with inflammatory rheumatic diseases and then translated it into 28 languages. Nineteen children (79% female, n= 15) and 17 parents participated. The mean age was 12 +/- 4 years, with median disease duration of 21 months (1-172 months). We translated SMILY (c)-Illness into the following 28 languages: Danish, Dutch, French (France), English (UK), German (Germany), German (Austria), German (Switzerland), Hebrew, Italian, Portuguese (Brazil), Slovene, Spanish (USA and Puerto Rico), Spanish (Spain), Spanish (Argentina), Spanish (Mexico), Spanish (Venezuela), Turkish, Afrikaans, Arabic (Saudi Arabia), Arabic (Egypt), Czech, Greek, Hindi, Hungarian, Japanese, Romanian, Serbian and Xhosa.Conclusion: SMILY (c)-Illness is a brief, easy to administer and score HRQOL scale for children with systemic rheumatic diseases. It is suitable for use across different age groups and literacy levels. SMILY (c)-Illness with its available translations may be used as useful adjuncts to clinical practice and research.